2020
DOI: 10.1021/acssuschemeng.0c02158
|View full text |Cite
|
Sign up to set email alerts
|

Single Atoms Anchored on Cobalt-Based Catalysts Derived from Hydrogels Containing Phthalocyanine toward the Oxygen Reduction Reaction

Abstract: Herein, a novel hydrogel-derived three-dimensional network-like nanostructured CoO X /Co–N–C­(800) catalyst was synthesized. CoO X nanoparticles are embedded on N-doped carbon with single Co atoms anchored after pyrolysis. The as-prepared CoO X /Co–N–C­(800) catalyst possesses excellent electrochemical performance toward the oxygen reduction reaction with a positive onset and half-wave potential of 0.95 and 0.88 V (vs RHE), respectively, including almost a four-electron pathway (3.97) and better durability co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 57 publications
(76 reference statements)
0
12
0
Order By: Relevance
“…The N 1s peaks in the spectra (Fig. 4c and g) can be divided into ve N types, pyridinic-N (398.2 eV), Fe-N (399.1 eV), pyrrolic-N (400.1 eV), graphitic-N (401.2 eV) and oxidized-N (402.9 eV), [39][40][41] and their relative content is shown in Table S3. † With the increase of the doping amount of melamine, the total content of N in the catalyst is 2.71%, 1.84%, 1.88%, 4.39%, 2.40% and 2.22%, respectively, which increases rst and then decreases.…”
Section: Resultsmentioning
confidence: 99%
“…The N 1s peaks in the spectra (Fig. 4c and g) can be divided into ve N types, pyridinic-N (398.2 eV), Fe-N (399.1 eV), pyrrolic-N (400.1 eV), graphitic-N (401.2 eV) and oxidized-N (402.9 eV), [39][40][41] and their relative content is shown in Table S3. † With the increase of the doping amount of melamine, the total content of N in the catalyst is 2.71%, 1.84%, 1.88%, 4.39%, 2.40% and 2.22%, respectively, which increases rst and then decreases.…”
Section: Resultsmentioning
confidence: 99%
“…[7] Since the pioneering work of Jasinski's cobalt phthalocyanine-derived ORR catalysts, [8] several other studies on non-precious metal-based catalysts, predominantly metalÀ NÀ C materials, have been explored. [9] It usually entails the synthesis of metal coordination molecules like phthalocyanine, [10] porphyrin [11] and corrole, [12] etc. The synthesis of such metal coordinating molecules is often impeded by complicated synthetic methods and frequently accompanied by poor yields.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Carbon-based transition metal catalysts with MÀ N4 (M = Fe, Co, Ni, Cu) active catalytic sites are of particular interest. [11][12][13][14] The high-temperature heat treatment of transition metals combined with carbon is a common means of generating MÀ N4 sites. During this process, transition metal atoms are anchored to the surface of a carbon-based substrate such that stable oxygen reduction sites are exposed.…”
Section: Introductionmentioning
confidence: 99%
“…Many current studies on transition metal single‐atom catalysts, such as the single‐atom Cu‐S 1 N 3 reported by Yu and his colleagues, have shown good catalytic activity [10] . Carbon‐based transition metal catalysts with M−N4 (M=Fe, Co, Ni, Cu) active catalytic sites are of particular interest [11–14] . The high‐temperature heat treatment of transition metals combined with carbon is a common means of generating M−N4 sites.…”
Section: Introductionmentioning
confidence: 99%